Molten salt electrochemical method for template-free preparation of silicon nanowire from nickel in-situ catalytic silicon waste
The molten salt electrochemical method of preparing silicon nanowires without templates by nickel in-situ catalytic silicon waste, using pulse current and high oxygen ion conductive separator, the problems of low electrolytic efficiency and unstable product quality in the existing technology are solved, and high efficiency is achieved Preparation of high-purity silicon nanowires improves the electrochemical performance of lithium batteries.
Patent Information
- Application Number
- CN202411703588.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
The existing molten salt electrolysis method for preparing metal catalytic silicon nanowires has problems such as single equipment structure, slow oxygen ion transmission efficiency, difficult control of reaction rate and material purity, resulting in low electrolytic efficiency and unstable product quality.
The molten salt electrochemical method of preparing silicon nanowires without templates by nickel in situ catalytic silicon waste is used to prepare silicon nanowires by step electrolysis of the peroxide additive through pulse current, increasing the conductive separator of high oxygen ion, improving molten salt electrolysis, and realizing nickel in situ catalytic without The template method is used to efficiently prepare high-purity silicon nanowires in one step.
It improves electrolytic efficiency, promotes uniform deposition of silicon, avoids the generation of by-products, improves the purity and mechanical stress of the product, and solves the structural failure problem caused by volume expansion during charging and discharging of lithium batteries.
Smart Images

Figure CN119465188A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a molten salt electrochemical method for preparing silicon nanowires without a template by using nickel in-situ catalytic silicon waste, and belongs to the technical field of material preparation. Background Art
[0002] With the rapid development of new energy vehicles and portable mobile devices, the demand for the service life, stability and safety of energy storage materials has been further improved. Due to the limitation of low capacity of graphite, silicon materials have high theoretical capacity (about 4200mAhg -1 ), moderate working voltage, abundant resource reserves, and environmental friendliness are recognized as the most promising lithium battery negative electrode material. However, due to the huge volume change (about ~300%) during the cycle of silicon negative electrode and its natural poor conductivity, the rate performance of silicon-based negative electrode is further limited. Studies have shown that nanoscale silicon particles can overcome the cracking and crushing caused by the rapid change in volume. Among them, silicon nanowires as a one-dimensional structure can expand longitudinally and radially, thereby avoiding the cracking stress that may be caused by two-dimensional or three-dimensional structures, avoiding structural failure and repeated formation of solid electrolyte membrane (SEI). In addition, silicon nanowires also have good conductivity, high interface area for contact with electrolytes, and short diffusion distance for lithium ion transmission, making them suitable for high-rate applications. Therefore, reasonable silicon nanowire structure design is helpful to further improve the electrochemical performance of silicon-based materials as lithium battery negative electrodes.
[0003] Precious metal catalysts have high catalytic activity and can effectively reduce the activation energy of the reaction. They also have excellent chemical and thermal stability and can work stably for a long time in high temperature, high pressure and corrosive environments. However, their high price and scarce resources greatly limit their large-scale application. Since the d-band electrons of transition metal nickel are not filled, the d-band holes formed have strong ability to capture and exchange electrons, showing excellent catalytic performance. In addition, nickel is cheap and has abundant resources, making it a major candidate material to replace precious metal catalysts. Compared with bulk or powdered nickel, nanoparticle-shaped metal nickel has a larger specific surface area, which can expose more reactive sites, thereby catalyzing the reaction more efficiently.
[0004] In the mainstream methods of traditional preparation of nanomaterials, whether it is gas phase growth method or liquid phase growth method, they are accompanied by complex process flow, high pollution, high production cost and high energy consumption, which makes it difficult to prepare nanomaterials on a large scale and efficiently. In recent years, the emerging molten salt electrolysis method uses oxides as raw materials and further electrolyzes and prepares nanomaterials with different morphologies and structures by regulating electrochemical parameters such as electrolysis process temperature, molten salt, and cell voltage. It not only shortens the process flow, but also reduces energy loss and environmental pollution.
[0005] However, the current molten salt electrolysis method for preparing metal-catalyzed silicon nanowires not only has a single equipment structure, that is, direct electrolysis is performed by inserting a cathode and an anode into the molten salt system at a certain electrolysis temperature, resulting in slow oxygen ion transmission efficiency. In addition, the lack of oxygen ions in the early stage of electrolysis has an adverse effect on the reaction rate, material purity, morphology, and size control, which ultimately affects the entire electrolysis process. Although the reaction rate can be increased to a certain extent by increasing the electrolysis voltage and increasing the overpotential to promote the reaction kinetics and accelerate the migration of oxygen ions, blindly increasing the voltage will lead to the continuous occurrence of side reactions, such as electrolyte decomposition or the generation of corrosive gases, which greatly affects the efficiency of the electrolysis process, product quality, equipment life, and the economy of the overall operation, and does not meet the requirements of large-scale production. Summary of the invention
[0006] In view of the above-mentioned problems existing in the existing molten salt electrolysis method for preparing metal-catalyzed silicon nanowires, the present invention proposes a molten salt electrochemical method for preparing silicon nanowires from silicon waste using nickel in situ catalysis without a template, that is, using silicon waste and a metal nickel-based catalyst as raw materials, performing step-by-step electrolysis with pulse current to assist peroxide additives, and adding a high oxygen ion conductive diaphragm to improve the molten salt electrolysis, so as to achieve the nickel in situ catalytic template-free method for efficiently preparing high-purity silicon nanowires in one step, while improving the electrolysis efficiency and promoting the uniform deposition of silicon, avoiding the generation of by-products, and effectively solving a series of severe challenges faced by negative electrode materials for lithium and sodium ion batteries.
[0007] Silica ash, also known as microsilica powder, is a very fine non-crystalline silicon dioxide (SiO2) silicon waste formed by volatilization and oxidation reaction in an arc furnace for producing silicon or silicon alloys. Silica ash mainly comes from the metallurgical and chemical industries. The silica ash particles are very fine, with an average particle size of 0.1 to 50 μm and a very high specific surface area. The present invention uses high-frequency pulse current to decompose peroxide additives, thereby avoiding the problems of difficulty in starting the electrolysis process and aggravated concentration polarization caused by insufficient oxygen ions in the early stage. At the same time, the high oxygen ion conductive diaphragm solves the voltage loss caused by the transmission of molten salt ions, improves the efficiency of the electrolysis process, and can effectively separate the cathode and anode regions to prevent side reactions. Finally, silicon nanowires are prepared. The growth end of the silicon nanowire is partially coated with a NiSi2 film, which has good mechanical stress. It can effectively solve the problem of structural failure caused by volume expansion during the charging and discharging process of lithium batteries and the repeated formation of solid electrolyte membranes (SEI). It has the advantages of low production cost, high product purity and simple process for industrial production.
[0008] A molten salt electrochemical method for preparing silicon nanowires from silicon waste by nickel in-situ catalysis without a template, the specific steps are as follows:
[0009] (1) dispersing a binder in deionized water, stirring at a temperature of 70 to 100° C. for 2 to 5 minutes to obtain a binder gel, grinding and mixing the binder gel with silicon waste to obtain a silicon waste-gel mixture, and sintering the silicon waste-gel mixture at a temperature of 100 to 200° C. for 5 to 20 minutes to obtain a bonding silicon material;
[0010] (2) Adding nickel catalyst and pore-forming agent to the bonding silicon material, grinding and mixing, and then pressing and molding to obtain an electrolytic precursor; preferably, the pressing pressure is 10-25 MPa, and the pressure holding time is 2-6 min; the thickness of the electrolytic precursor is 1-5 mm.
[0011] (3) adding a peroxide additive to a molten salt electrolyte, uniformly heating the temperature to 500 to 800° C. in a vacuum or protective gas atmosphere and maintaining the temperature until the molten salt electrolyte is completely dissolved into a molten state, thereby obtaining a molten salt electrolyte;
[0012] (4) using an electrolytic precursor as a reduction cathode and an inert electrode as an anode, using a porous solid oxide diaphragm to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell, filling the anode electrolytic cell and the cathode electrolytic cell with molten salt electrolyte, inserting the reduction cathode into the molten salt electrolyte of the cathode electrolytic cell, and inserting the anode into the molten salt electrolyte of the anode electrolytic cell;
[0013] (5) At a temperature of 700 to 900° C., electrolyze the molten salt for 5 to 25 minutes with a high-frequency pulse current (to efficiently decompose peroxides) and a low duty cycle (the low duty cycle allows the electrode surface to have sufficient time to react and diffuse, thereby reducing concentration polarization), then electrolyze the molten salt for 40 to 120 minutes with a medium-frequency pulse current and a medium duty cycle to make the electrode surface reaction process more complete and stable, thereby reducing electrode loss caused by excessive local current density, and then electrolyze the molten salt for 80 to 200 minutes with a low-frequency pulse current and a high duty cycle to ensure a stable and continuous electrolysis reaction, and extend the current on time to maximize the electrode reaction efficiency; the frequency of the high-frequency pulse current is 1500 to 2000 Hz, and the low duty cycle is 10 to 16%; the frequency of the medium-frequency pulse current is 1 / 5 to 2 / 5 of the high-frequency pulse current, and the medium duty cycle is 1.6 to 2 times that of the low duty cycle; the frequency of the low-frequency pulse current is 1 / 30 to 1 / 8 of the medium-frequency pulse current, and the high duty cycle is 2 to 2.5 times that of the medium duty cycle;
[0014] Preferably, the frequency of the medium frequency pulse current is 300-800 Hz, and the medium duty cycle is 16-32%; the frequency of the low frequency pulse current is 10-100 Hz, and the high duty cycle is 32-80%;
[0015] (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment, water washing, soaking and acid washing, and drying in sequence to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film.
[0016] Preferably, the binder in step (1) is one or more of epoxy resin, polyurethane, acrylate, silicone glue, polyvinyl alcohol, water glass, aluminum phosphate, and polyamide, and the mass ratio of the binder to the silicon waste is (32-48):100; the silicon waste is silicon ash in the production process of industrial silicon or silicon alloy, and the morphology is amorphous silica microspheres with an average particle size of 0.1-50 μm.
[0017] Preferably, the nickel catalyst in step (2) is one or more of nickel (II) acetylacetone, nickel oxide, nickel chloride, nickel formate, and nickel dichloride (diphenylphosphinoethane); the pore-forming agent is one or more of urea, CaCl2, starch, polystyrene, (NH4)2SO4, and NH4HCO3.
[0018] More preferably, the mass ratio of the silica fume in step (1) to the nickel catalyst and pore-forming agent in step (2) is 100:(2-8):(12-18).
[0019] Preferably, the peroxide additive in step (3) is one or more of sodium peroxide, potassium peroxide, magnesium peroxide, lithium peroxide, and strontium peroxide, and the amount of the peroxide additive added is 4 to 8 wt.% of the molten salt electrolyte.
[0020] Preferably, the molten salt electrolyte is one or more of chloride, fluoride, carbonate and nitrate.
[0021] Preferably, the protective gas in step (3) is helium, argon, nitrogen, neon or krypton.
[0022] Preferably, the material of the inert electrode in step (4) is one or more of platinum, graphite, glassy carbon, ruthenium oxide, and iridium oxide; the porous solid oxide diaphragm is yttrium-stabilized zirconium oxide (YSZ), calcium-stabilized zirconium oxide (CSZ), or lithium aluminum zircon phosphate (LAGP), with a porosity of 32-40% and a pore size of 0.01-0.1 μm.
[0023] Preferably, in step (4), the distance between the anode and the cathode is 15 to 45 mm.
[0024] Preferably, the ultrasonic power of step (6) is 500-1500w, and the time is 1-10min; the acid solution for pickling is one or more of HCl, H2SO4, HNO3, and HF, and the H + The concentration is 0.01~10mol / L, and the immersion pickling time is 0.5~4h.
[0025] The beneficial effects of the present invention are:
[0026] (1) The present invention is based on the extremely fine natural particle size of silica ash micro-spherical particles, which avoids the pre-treatment process of silicon materials such as silicon dioxide and cut silicon waste that requires ball milling to reduce the particle size. The main component of silica ash is SiO 2, The molten salt electrolysis can be directly carried out without unnecessary oxidation regulation, which simplifies the process flow; its high specific surface area can provide more active sites for the reaction, greatly improving the efficiency and catalytic activity of the electrolysis, promoting the nucleation and growth process of the nanowires, and realizing the efficient preparation of nanowires;
[0027] (2) The present invention solves the problems of difficulty in starting the electrolysis, uneven silicon deposition, and corrosive gas generation caused by side reactions due to insufficient oxygen ions in the initial stage of electrolysis by designing a pulse current step-by-step electrolysis auxiliary peroxide additive, thereby ensuring that oxygen ions are always sufficient during the entire electrolysis process. At the same time, the high oxygen ion conductive diaphragm also improves the shortcomings of molten salt electrolysis technology, reduces the voltage loss caused by ion transport during the electrolysis process, avoids the aggravation of concentration polarization caused by the oxygen ion generation rate being greater than the oxygen ion transport rate during the electrolysis process, and improves the efficiency of the electrolysis process. In addition, it can effectively separate the cathode and anode regions to prevent side reactions from increasing the purity of the product; the method of the present invention is simple to operate, avoids environmental pollution caused by chemical reagents, and the molten salt used for electrolysis can be reused, providing a guiding idea for expanding production and realizing industrialization;
[0028] (3) The present invention can prepare silicon nanowires in one step without a template. During the molten salt electrolysis process, micron nickel and micron silicon balls are first sintered into nano-scale nickel and silicon particles at a certain temperature, and finally form NiSi2 alloy particles; as the temperature rises, the NiSi2 alloy particles will gradually form NiSi2 alloy droplets. When Si is gradually precipitated after the droplets reach saturation, they will continue to grow into silicon nanowires with alloy droplet growth ends. Therefore, the NiSi2 alloy droplets are the key to the nucleation and growth of nanowires; after the silicon nanowires grow to a certain length, the diffusion rate of the alloy droplets will increase at high temperatures, making them easier to move and contact. At the same time, the van der Waals force between the nano alloy particles makes them easier to approach and adhere to each other. Finally, the nano NiSi2 alloy droplets gather at the growth end of the silicon nanowire to form a certain cluster, which is manifested as a layer of NiSi2 film locally coated, further enhancing the mechanical stress of the silicon nanowire, and can well suppress the problem of volume expansion (>300%) of the nanowire during the charging and discharging process of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the molten salt electrochemical method for preparing silicon nanowires from silicon waste without template by in-situ catalysis of nickel; in the figure, 1-cathode, 2-alumina crucible, 3-porous solid oxide diaphragm, 4-molten salt system, 5-electrolysis precursor, 6-anode;
[0030] Figure 2 The XRD diagram of the raw material silicon ash and the electrolysis product silicon nanowires in Example 1;
[0031] Figure 3 This is a partial SEM magnified image of the electrolysis product silicon nanowires of Example 1;
[0032] Figure 4 This is an EDS image of the electrolysis product silicon nanowires of Example 1;
[0033] Figure 5 This is a cycle performance diagram of the lithium battery silicon negative electrode of Example 2. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0035] Example 1: A molten salt electrochemical method for preparing silicon nanowires from silicon waste without a template using nickel in situ catalysis (see Figure 1 ), the specific steps are as follows:
[0036] (1) dispersing a binder (epoxy resin) in deionized water, stirring at 70° C. for 2 min to obtain a binder gel, grinding and mixing the binder gel with silicon waste (spherical silicon ash with an average particle size of 0.1 μm) to obtain a silicon waste-gel mixture, and sintering the silicon waste-gel mixture at 120° C. for 5 min to obtain a bonding silicon material;
[0037] (2) adding a nickel catalyst (nickel (II) acetylacetone) and a pore-forming agent (urea) to the bonding silicon material, grinding and mixing, and then pressing and molding at a pressure of 10 MPa for 2 minutes to obtain an electrolytic precursor (circular structure) with a thickness of 1 mm; the mass ratio of the silicon waste, the binder (epoxy resin), the pore-forming agent (urea) and the nickel catalyst (nickel (II) acetylacetone) is 100:32:18:6;
[0038] (3) adding a peroxide additive (potassium peroxide) to a molten salt electrolyte (NaNO3-NaCl binary molten salt electrolyte system), uniformly heating the temperature to 500°C at a heating rate of 4°C / min under vacuum and keeping the temperature for 30 min until the molten salt electrolyte (NaNO3 and NaCl) are completely dissolved into a molten state, thereby obtaining a molten salt electrolyte; the mass ratio of NaNO3 to NaCl is 1:2, and the amount of the peroxide additive (potassium peroxide) added is 4wt.% of the molten salt electrolyte (NaNO3-NaCl binary molten salt electrolyte system);
[0039] (4) The electrolytic precursor is closely attached to a molybdenum sheet of the same size, and then tied to a cathode current collector molybdenum rod by a molybdenum wire as a reduction cathode, an inert electrode (platinum electrode) is used as an anode, and a porous solid oxide diaphragm (YSZ) is used to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell. The anode electrolytic cell and the cathode electrolytic cell are filled with molten salt electrolyte, the reduction cathode is inserted into the molten salt electrolyte of the cathode electrolytic cell, and the anode is inserted into the molten salt electrolyte of the anode electrolytic cell; the distance between the anode and the cathode is 15 mm;
[0040] (5) At a temperature of 750°C, the molten salt was electrolyzed for 15 minutes with a high-frequency pulse current of 1500 Hz (to efficiently decompose peroxides) and a duty cycle of 10% (a low duty cycle allows sufficient time for the electrode surface to react and diffuse, reducing concentration polarization), and then the molten salt was electrolyzed for 55 minutes with a medium-frequency pulse current of 350 Hz and a duty cycle of 24% to make the electrode surface reaction process more complete and stable, reduce the electrode loss caused by excessive local current density, and then the molten salt was electrolyzed for 90 minutes with a low-frequency pulse current of 50 Hz and a duty cycle of 70% to ensure a stable and continuous electrolysis reaction and extend the current on time to maximize the electrode reaction efficiency;
[0041] (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment with a power of 500 W for 1 min, washed with deionized water for 5 min, stirred and soaked in a 0.1 mol / L hydrochloric acid solution for acid washing for 1 h, solid-liquid separation, and solid drying to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film;
[0042] The XRD patterns of the silicon waste raw material and the silicon nanowires produced by electrolysis in this example are shown in Figure 2 ,from Figure 2 It can be seen that the XRD pattern of the electrolysis product clearly shows the dominant peaks of crystalline silicon (JCPDS No. 78-2500) and NiSi2 (JCPDS No. 65-2974), corresponding to the diamond cubic structure and cubic fluorite structure, respectively, proving the formation of crystalline silicon and NiSi2 phases. Due to the high lattice matching of crystalline silicon and NiSi2, the XRD diffraction patterns of crystalline silicon and NiSi2 basically overlap in the range of 10° to 90°. No other impurity peaks were observed, proving that the prepared material has a high purity;
[0043] The SEM partial enlarged image of the electrolysis product silicon nanowires in this example is shown in Figure 3 ,from Figure 3It can be seen that there are some straight and curved silicon nanowires in the figure. The straight silicon nanowires are attributed to the NiSi2 alloy droplets as crystal nuclei to form an ordered lattice structure and a stable reaction interface to promote the directional deposition of silicon, and tend to be straight during the growth process; while the curved silicon nanowires may be due to the uneven deposition caused by the lack of NiSi2 catalysis on the surface, resulting in curved growth. These two different forms of silicon nanowires formed by molten salt electrolysis can effectively alleviate the volume change of silicon negative electrode during lithiation and delithiation;
[0044] The EDS image of the electrolysis product silicon nanowires in this example is shown in Figure 4 ,from Figure 4 It can be seen that the distribution of Si and Ni elements provides strong support for the formation of silicon nanowires and NiSi2 alloy droplets, as shown in the figure. Because the increased diffusion rate of alloy droplets at high temperature makes them easier to move and contact, and the van der Waals attraction between nano alloy particles makes them easier to approach and adhere to each other. Finally, the nano NiSi2 alloy droplets agglomerate at the growth end of the silicon nanowire to form a certain cluster, forming a layer of NiSi2 film that is partially coated, which is shown in the figure as a local concentrated distribution of Ni elements; the presence of O element spots may be caused by slight surface oxidation of the sample;
[0045] The silicon nanowires prepared in this embodiment were used as the silicon negative electrode material for lithium batteries to test their electrochemical properties. The testing method was carried out in accordance with the method in Appendix D of the national standard GB / T38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode was 724.32 mAh / g, and the first coulombic efficiency could reach 87.13%.
[0046] Example 2: A molten salt electrochemical method for preparing silicon nanowires from silicon waste using nickel in situ catalysis without a template (see Figure 1 ), the specific steps are as follows:
[0047] (1) dispersing a binder (polyurethane) in deionized water, stirring at 75° C. for 3 min to obtain a binder gel, grinding and mixing the binder gel with silicon waste (spherical silicon ash with an average particle size of 1 μm) to obtain a silicon waste-gel mixture, and sintering the silicon waste-gel mixture at 170° C. for 7 min to obtain a bonding silicon material;
[0048] (2) adding a nickel catalyst (nickel oxide) and a pore-forming agent (CaCl2) to the bonding silicon material, grinding and mixing, and then pressing and molding at a pressure of 12 MPa for 3 minutes to obtain an electrolytic precursor (circular structure) with a thickness of 1 mm; the mass ratio of the silicon waste, the bonding agent (polyurethane), the pore-forming agent (CaCl2) and the nickel catalyst (nickel oxide) is 100:40:15:8;
[0049] (3) adding a peroxide additive (strontium peroxide) to a molten salt electrolyte (KNO3-KCl binary molten salt electrolyte system), uniformly heating the temperature to 520°C at a heating rate of 5°C / min in a helium atmosphere and keeping the temperature for 36 minutes until the molten salt electrolyte (KNO3 and KCl) are completely dissolved into a molten state, thereby obtaining a molten salt electrolyte; the mass ratio of KNO3 to KCl is 1:1, and the amount of the peroxide additive (strontium peroxide) added is 6wt.% of the molten salt electrolyte (KNO3-KCl binary molten salt electrolyte system);
[0050] (4) The electrolytic precursor is closely fitted with a molybdenum sheet of the same size, and then tied to a cathode current collector molybdenum rod by a molybdenum wire as a reduction cathode, an inert electrode (graphite electrode) is used as an anode, and a porous solid oxide diaphragm (CSZ) is used to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell. The anode electrolytic cell and the cathode electrolytic cell are filled with molten salt electrolyte, the reduction cathode is inserted into the molten salt electrolyte of the cathode electrolytic cell, and the anode is inserted into the molten salt electrolyte of the anode electrolytic cell; the distance between the anode and the cathode is 16 mm;
[0051] (5) At a temperature of 900°C, the molten salt was electrolyzed for 20 minutes with a high-frequency pulse current of 1700 Hz (to efficiently decompose peroxides) and a duty cycle of 15% (a low duty cycle allows sufficient time for the electrode surface to react and diffuse, reducing concentration polarization), and then the molten salt was electrolyzed for 60 minutes with a medium-frequency pulse current of 400 Hz and a duty cycle of 20% to make the electrode surface reaction process more complete and stable, reduce the electrode loss caused by excessive local current density, and then the molten salt was electrolyzed for 120 minutes with a low-frequency pulse current of 85 Hz and a duty cycle of 65% to ensure a stable and continuous electrolysis reaction and extend the current on time to maximize the electrode reaction efficiency;
[0052] (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment with a power of 800 W for 2 min, washed with deionized water for 5 min, stirred and soaked in a 0.2 mol / L hydrochloric acid solution for acid washing for 0.5 h, solid-liquid separation, and solid drying to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film;
[0053] The silicon nanowires prepared in this embodiment were used as the silicon negative electrode material for lithium batteries to test their electrochemical properties. The test method was carried out in accordance with the method in Appendix D of the national standard GB / T38823-2020. Figure 5 As shown, the first discharge specific capacity of the lithium battery silicon negative electrode is 705.84 mAh / g, and the first coulombic efficiency can reach 87.54%.
[0054] Example 3: A molten salt electrochemical method for preparing silicon nanowires from silicon waste using nickel in situ catalysis without a template (see Figure 1 ), the specific steps are as follows:
[0055] (1) dispersing a binder (acrylate) in deionized water, stirring at 80° C. for 4 min to obtain a binder gel, grinding and mixing the binder gel with silicon waste (spherical silicon ash with an average particle size of 50 μm) to obtain a silicon ash-gel mixture, and sintering the silicon ash-gel mixture at 120° C. for 9 min to obtain a bonding silicon material;
[0056] (2) adding a nickel catalyst (nickel chloride) and a pore-forming agent (starch) to the bonding silicon material, grinding and mixing, and then pressing and molding at a pressure of 10 MPa for 4 minutes to obtain an electrolytic precursor (circular structure) with a thickness of 2 mm; the mass ratio of the silicon ash, the binder (acrylate), the pore-forming agent (starch) and the nickel catalyst (nickel chloride) is 100:36:12:10;
[0057] (3) adding a peroxide additive (lithium peroxide) to a molten salt electrolyte (CaCl2-KCl binary molten salt electrolyte system), uniformly heating the temperature to 550°C at a heating rate of 7°C / min under a nitrogen atmosphere and keeping the temperature for 30 min until the molten salt electrolyte (CaCl2 and KCl) are completely dissolved into a molten state, thereby obtaining a molten salt electrolyte; the mass ratio of CaCl2 to KCl is 3:1, and the amount of the peroxide additive (lithium peroxide) added is 7wt.% of the molten salt electrolyte (CaCl2-KCl binary molten salt electrolyte system);
[0058] (4) The electrolytic precursor is closely attached to a molybdenum sheet of the same size, and then tied to a cathode current collector molybdenum rod by a molybdenum wire as a reduction cathode, an inert electrode (glassy carbon) is used as an anode, and a porous solid oxide diaphragm (LAGP) is used to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell. The anode electrolytic cell and the cathode electrolytic cell are filled with molten salt electrolyte, the reduction cathode is inserted into the molten salt electrolyte of the cathode electrolytic cell, and the anode is inserted into the molten salt electrolyte of the anode electrolytic cell; the distance between the anode and the cathode is 20 mm;
[0059] (5) At a temperature of 800°C, the molten salt was electrolyzed for 20 minutes with a high-frequency pulse current of 1550 Hz (to efficiently decompose peroxides) and a duty cycle of 15% (a low duty cycle allows sufficient time for the electrode surface to react and diffuse, reducing concentration polarization), and then the molten salt was electrolyzed for 60 minutes with a medium-frequency pulse current of 350 Hz and a duty cycle of 30% to make the electrode surface reaction process more complete and stable, reduce the electrode loss caused by excessive local current density, and then the molten salt was electrolyzed for 130 minutes with a low-frequency pulse current of 60 Hz and a duty cycle of 76% to ensure a stable and continuous electrolysis reaction and extend the current on time to maximize the electrode reaction efficiency;
[0060] (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment with a power of 1000 W for 4 minutes, washed with deionized water for 6 minutes, stirred and soaked in a 1 mol / L hydrochloric acid solution for acid washing for 1 hour, solid-liquid separation, and solid drying to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film;
[0061] The silicon nanowires prepared in this embodiment were used as the silicon negative electrode material for lithium batteries to test their electrochemical properties. The testing method was carried out in accordance with the method in Appendix D of the national standard GB / T38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode was 685.62 mAh / g, and the first coulombic efficiency could reach 87.47%.
[0062] Example 4: A molten salt electrochemical method for preparing silicon nanowires from silicon waste using nickel in situ catalysis without a template (see Figure 1 ), the specific steps are as follows:
[0063] (1) dispersing a binder (silicone gel) in deionized water, stirring at 85° C. for 5 min to obtain a binder gel, grinding and mixing the binder gel with silicon waste (spherical silicon ash with an average particle size of 10 μm) to obtain a silicon ash-gel mixture, and sintering the silicon ash-gel mixture at 130° C. for 10 min to obtain a bonding silicon material;
[0064] (2) Adding nickel catalyst (nickel formate) and pore former (NH4HCO3) to the bonding silicon material, grinding and mixing, and then pressing and molding at a pressure of 22 MPa for 2 minutes to obtain an electrolytic precursor (circular structure) with a thickness of 3 mm; the mass ratio of the silica ash, the binder (silicone glue), the pore former (NH4HCO3) and the nickel catalyst (nickel formate) is 100:42:12:12;
[0065] (3) adding a peroxide additive (sodium peroxide) to a molten salt electrolyte (CaCl2-NaCl binary molten salt electrolyte system), uniformly heating the temperature to 600°C at a heating rate of 5°C / min under an argon atmosphere and keeping the temperature for 48 min until the molten salt electrolyte (CaCl2 and NaCl) are completely dissolved into a molten state, thereby obtaining a molten salt electrolyte; the mass ratio of CaCl2 to NaCl is 2:1, and the amount of the peroxide additive (sodium peroxide) added is 5wt.% of the molten salt electrolyte (CaCl2-NaCl binary molten salt electrolyte system);
[0066] (4) The electrolytic precursor is closely attached to a molybdenum sheet of the same size, and then tied to a cathode current collector molybdenum rod by a molybdenum wire as a reduction cathode, an inert electrode (ruthenium oxide) is used as an anode, and a porous solid oxide diaphragm (CSZ) is used to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell. The anode electrolytic cell and the cathode electrolytic cell are filled with molten salt electrolyte, the reduction cathode is inserted into the molten salt electrolyte of the cathode electrolytic cell, and the anode is inserted into the molten salt electrolyte of the anode electrolytic cell; the distance between the anode and the cathode is 22 mm;
[0067] (5) At a temperature of 850°C, the molten salt was electrolyzed for 25 minutes with a high-frequency pulse current of 1600 Hz (to efficiently decompose peroxides) and a duty cycle of 12% (a low duty cycle allows sufficient time for the electrode surface to react and diffuse, reducing concentration polarization), and then the molten salt was electrolyzed for 75 minutes with a medium-frequency pulse current of 300 Hz and a duty cycle of 22% to make the electrode surface reaction process more complete and stable, reduce the electrode loss caused by excessive local current density, and then the molten salt was electrolyzed for 90 minutes with a low-frequency pulse current of 55 Hz and a duty cycle of 80% to ensure a stable and continuous electrolysis reaction and extend the current on time to maximize the electrode reaction efficiency;
[0068] (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment with a power of 1500 W for 6 min, washed with deionized water for 10 min, stirred and soaked in a 1.5 mol / L hydrochloric acid solution for acid washing for 1.5 h, solid-liquid separation, and solid drying to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film;
[0069] The silicon nanowires prepared in this embodiment were used as the silicon negative electrode material for lithium batteries to test their electrochemical properties. The testing method was carried out in accordance with the method in Appendix D of the national standard GB / T38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode was 755.94 mAh / g, and the first coulombic efficiency could reach 85.32%.
[0070] Example 5: A molten salt electrochemical method for preparing silicon nanowires from silicon waste using nickel in situ catalysis without a template (see Figure 1 ), the specific steps are as follows:
[0071] (1) dispersing a binder (polyvinyl alcohol) in deionized water, stirring at 90° C. for 4 min to obtain a binder gel, grinding and mixing the binder gel with silica fume (spherical silica fume with an average particle size of 30 μm) to obtain a silica fume-gel mixture, and sintering the silica fume-gel mixture at 130° C. for 12 min to obtain a bonding silicon material;
[0072] (2) Adding nickel catalyst (nickel dichloride of bis(diphenylphosphinoethane)) and pore former (urea) to the bonding silicon material, grinding and mixing, and then pressing and molding at a pressure of 24 MPa for 3 minutes to obtain an electrolytic precursor (circular structure) with a thickness of 4 mm; the mass ratio of the silicon ash, the binder (polyvinyl alcohol), the pore former (urea) and the nickel catalyst (nickel dichloride of bis(diphenylphosphinoethane)) is 100:44:13:8;
[0073] (3) adding a peroxide additive (magnesium peroxide) to a molten salt electrolyte (Na2CO3-NaCl binary molten salt electrolyte system), uniformly heating the temperature to 650°C at a heating rate of 7°C / min in a neon atmosphere and keeping the temperature for 60 min until the molten salt electrolyte (Na2CO3 and NaCl) is completely dissolved into a molten state, thereby obtaining a molten salt electrolyte; the mass ratio of Na2CO3 to NaCl is 1:1, and the amount of the peroxide additive (magnesium peroxide) added is 7wt.% of the molten salt electrolyte (Na2CO3-NaCl binary molten salt electrolyte system);
[0074] (4) The electrolytic precursor is closely attached to a molybdenum sheet of the same size, and then tied to a cathode current collector molybdenum rod by a molybdenum wire as a reduction cathode, an inert electrode (graphite) is used as an anode, and a porous solid oxide diaphragm (a mixed diaphragm of CSZ and LAGP) is used to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell. The anode electrolytic cell and the cathode electrolytic cell are filled with molten salt electrolyte, the reduction cathode is inserted into the molten salt electrolyte of the cathode electrolytic cell, and the anode is inserted into the molten salt electrolyte of the anode electrolytic cell; the distance between the anode and the cathode is 23 mm;
[0075] (5) At a temperature of 700°C, the molten salt was electrolyzed for 25 minutes with a high-frequency pulse current of 1660 Hz (to efficiently decompose peroxides) and a duty cycle of 10% (a low duty cycle allows sufficient time for the electrode surface to react and diffuse, reducing concentration polarization), and then the molten salt was electrolyzed for 60 minutes with a medium-frequency pulse current of 350 Hz and a duty cycle of 18% to make the electrode surface reaction process more complete and stable, reduce the electrode loss caused by excessive local current density, and then the molten salt was electrolyzed for 100 minutes with a low-frequency pulse current of 70 Hz and a duty cycle of 60% to ensure a stable and continuous electrolysis reaction and extend the current on time to maximize the electrode reaction efficiency;
[0076] (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment at a power of 700 W for 8 minutes, washed with deionized water for 15 minutes, stirred and soaked in a 4 mol / L hydrochloric acid solution for acid washing for 3 hours, solid-liquid separation, and solid drying to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film;
[0077] The silicon nanowires prepared in this embodiment were used as the silicon negative electrode material for lithium batteries to test their electrochemical properties. The testing method was carried out in accordance with the method in Appendix D of the national standard GB / T38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode was 732.46 mAh / g, and the first coulombic efficiency could reach 84.28%.
[0078] Example 6: A molten salt electrochemical method for preparing silicon nanowires from silicon waste without template by in-situ catalysis of nickel (see Figure 1 ), the specific steps are as follows:
[0079] (1) dispersing a binder (water glass) in deionized water, stirring at 92° C. for 5 min to obtain a binder gel, grinding and mixing the binder gel with silicon waste (spherical silicon ash with an average particle size of 20 μm) to obtain a silicon ash-gel mixture, and sintering the silicon ash-gel mixture at 145° C. for 15 min to obtain a bonding silicon material;
[0080] (2) adding a nickel catalyst (nickel formate) and a pore former (CaCl2) to the bonding silicon material, grinding and mixing, and then pressing and molding at a pressure of 25 MPa for 2 minutes to obtain an electrolytic precursor (circular structure) with a thickness of 5 mm; the mass ratio of the silica fume, the binder (water glass), the pore former (CaCl2) and the nickel catalyst (nickel formate) is 100:38:16:6;
[0081] (3) adding a peroxide additive (sodium peroxide) to a molten salt electrolyte (MgCl2-K2CO3-KNO3 ternary molten salt electrolyte system), uniformly heating the temperature to 700°C at a heating rate of 6°C / min in a xenon atmosphere and keeping the temperature for 18 minutes until the molten salt electrolyte (MgCl2, K2CO3 and KNO3) is completely dissolved into a molten state, thereby obtaining a molten salt electrolyte; the mass ratio of MgCl2, K2CO3 and KNO3 is 1:2, and the amount of the peroxide additive (sodium peroxide) added is 5wt.% of the molten salt electrolyte (MgCl2-K2CO3-KNO3 ternary molten salt electrolyte system);
[0082] (4) The electrolytic precursor is closely attached to a molybdenum sheet of the same size, and then tied to a cathode current collector molybdenum rod by a molybdenum wire as a reduction cathode, an inert electrode (platinum) is used as an anode, and a porous solid oxide diaphragm (LAGP) is used to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell. The anode electrolytic cell and the cathode electrolytic cell are filled with molten salt electrolyte, the reduction cathode is inserted into the molten salt electrolyte of the cathode electrolytic cell, and the anode is inserted into the molten salt electrolyte of the anode electrolytic cell; the distance between the anode and the cathode is 28 mm;
[0083] (5) At a temperature of 900°C, the molten salt was electrolyzed for 22 minutes with a high-frequency pulse current of 1800 Hz (to efficiently decompose peroxides) and a duty cycle of 12% (a low duty cycle allows sufficient time for the electrode surface to react and diffuse, reducing concentration polarization), and then the molten salt was electrolyzed for 60 minutes with a medium-frequency pulse current of 400 Hz and a duty cycle of 30% to make the electrode surface reaction process more complete and stable, reduce the electrode loss caused by excessive local current density, and then the molten salt was electrolyzed for 180 minutes with a low-frequency pulse current of 90 Hz and a duty cycle of 76% to ensure a stable and continuous electrolysis reaction and extend the current on time to maximize the electrode reaction efficiency;
[0084] (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment with a power of 1200 W for 9 minutes, washed with deionized water for 16 minutes, stirred and soaked in a 6 mol / L hydrochloric acid solution for acid washing for 1 hour, solid-liquid separation, and solid drying to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film;
[0085] The silicon nanowires prepared in this embodiment were used as the silicon negative electrode material for lithium batteries to test their electrochemical properties. The testing method was carried out in accordance with the method in Appendix D of the national standard GB / T38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode was 664.67 mAh / g, and the first coulombic efficiency could reach 87.15%.
[0086] Example 7: A molten salt electrochemical method for preparing silicon nanowires from silicon waste using nickel in situ catalysis without a template (see Figure 1 ), the specific steps are as follows:
[0087] (1) dispersing a binder (acrylate) in deionized water, stirring at 95° C. for 4 min to obtain a binder gel, grinding and mixing the binder gel with silicon waste (spherical silicon ash with an average particle size of 0.1 μm) to obtain a silicon ash-gel mixture, and sintering the silicon ash-gel mixture at 170° C. for 16 min to obtain a bonding silicon material;
[0088] (2) adding a nickel catalyst (nickel oxide) and a pore-forming agent (NH4HCO3) to the bonding silicon material, grinding and mixing, and then pressing and molding at a pressure of 20 MPa for 3 minutes to obtain an electrolytic precursor (circular structure) with a thickness of 4 mm; the mass ratio of the silica fume, the binder (acrylate), the pore-forming agent (NH4HCO3) and the nickel catalyst (nickel oxide) is 100:48:12:7;
[0089] (3) adding a peroxide additive (lithium peroxide) to a molten salt electrolyte (MgCl2-CaCO3 binary molten salt electrolyte system), uniformly heating the temperature to 750°C at a heating rate of 4°C / min under an argon atmosphere and keeping the temperature for 30 min until the molten salt electrolyte (MgCl2 and CaCO3) are completely dissolved into a molten state, thereby obtaining a molten salt electrolyte; the mass ratio of MgCl2 to CaCO3 is 3:1, and the amount of the peroxide additive (lithium peroxide) added is 8wt.% of the molten salt electrolyte (MgCl2-CaCO3 binary molten salt electrolyte system);
[0090] (4) The electrolytic precursor is closely attached to a molybdenum sheet of the same size, and then tied to a cathode current collector molybdenum rod by a molybdenum wire as a reduction cathode, an inert electrode (graphite) is used as an anode, and a porous solid oxide diaphragm (a mixed diaphragm of LAGP and YSZ) is used to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell. The anode electrolytic cell and the cathode electrolytic cell are filled with molten salt electrolyte, the reduction cathode is inserted into the molten salt electrolyte of the cathode electrolytic cell, and the anode is inserted into the molten salt electrolyte of the anode electrolytic cell; the distance between the anode and the cathode is 35 mm;
[0091] (5) At a temperature of 750°C, the molten salt was electrolyzed for 15 minutes with a high-frequency pulse current of 1600 Hz (to efficiently decompose peroxides) and a duty cycle of 15% (a low duty cycle allows sufficient time for the electrode surface to react and diffuse, reducing concentration polarization), and then the molten salt was electrolyzed for 80 minutes with a medium-frequency pulse current of 600 Hz and a duty cycle of 60% to make the electrode surface reaction process more complete and stable, reduce the electrode loss caused by excessive local current density, and then the molten salt was electrolyzed for 160 minutes with a low-frequency pulse current of 75 Hz and a duty cycle of 70% to ensure a stable and continuous electrolysis reaction and extend the current on time to maximize the electrode reaction efficiency;
[0092] (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment at a power of 900 W for 9 minutes, washed with deionized water for 16 minutes, stirred and soaked in a hydrochloric acid solution with a concentration of 8 mol / L for acid washing for 0.6 hours, solid-liquid separation, and solid drying to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film;
[0093] The silicon nanowires prepared in this embodiment were used as the silicon negative electrode material for lithium batteries to test their electrochemical properties. The testing method was carried out in accordance with the method in Appendix D of the national standard GB / T38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode was 673.25 mAh / g, and the first coulombic efficiency could reach 86.84%.
[0094] Example 8: A molten salt electrochemical method for preparing silicon nanowires from silicon waste without a template using nickel in situ catalysis (see Figure 1 ), the specific steps are as follows:
[0095] (1) dispersing a binder (polyurethane) in deionized water, stirring at 100° C. for 5 min to obtain a binder gel, grinding and mixing the binder gel with silicon waste (spherical silicon ash with an average particle size of 40 μm) to obtain a silicon ash-gel mixture, and sintering the silicon ash-gel mixture at 150° C. for 20 min to obtain a bonding silicon material;
[0096] (2) adding a nickel catalyst (nickel chloride) and a pore former (polystyrene) to the bonding silicon material, grinding and mixing, and then pressing and molding at a pressure of 16 MPa for 5 minutes to obtain an electrolytic precursor (circular structure) with a thickness of 3 mm; the mass ratio of the silica fume, the binder (polyurethane), the pore former (polystyrene) and the nickel catalyst (nickel chloride) is 100:34:14:8;
[0097] (3) adding a peroxide additive (sodium peroxide) to a molten salt electrolyte (KNO3-ZnCl2 binary molten salt electrolyte system), uniformly heating the temperature to 800°C at a heating rate of 3°C / min under a nitrogen atmosphere and keeping the temperature for 60 min until the molten salt electrolyte (KNO3 and ZnCl2) are completely dissolved into a molten state, thereby obtaining a molten salt electrolyte; the mass ratio of KNO3 to ZnCl2 is 1:3, and the amount of the peroxide additive (sodium peroxide) added is 6 wt.% of the molten salt electrolyte (KNO3-ZnCl2 binary molten salt electrolyte system);
[0098] (4) The electrolytic precursor is closely fitted with a molybdenum sheet of the same size, and then tied to a cathode current collector molybdenum rod by a molybdenum wire as a reduction cathode, an inert electrode (graphite) is used as an anode, and a porous solid oxide diaphragm (YSZ) is used to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell. The anode electrolytic cell and the cathode electrolytic cell are filled with molten salt electrolyte, the reduction cathode is inserted into the molten salt electrolyte of the cathode electrolytic cell, and the anode is inserted into the molten salt electrolyte of the anode electrolytic cell; the distance between the anode and the cathode is 32 mm;
[0099] (5) At a temperature of 800°C, the molten salt was electrolyzed for 20 minutes with a high-frequency pulse current of 1600 Hz (to efficiently decompose peroxides) and a duty cycle of 16% (a low duty cycle allows sufficient time for the electrode surface to react and diffuse, reducing concentration polarization), and then the molten salt was electrolyzed for 70 minutes with a medium-frequency pulse current of 380 Hz and a duty cycle of 28% to make the electrode surface reaction process more complete and stable, reduce the electrode loss caused by excessive local current density, and then the molten salt was electrolyzed for 110 minutes with a low-frequency pulse current of 100 Hz and a duty cycle of 74%, to ensure a stable and continuous electrolysis reaction and extend the current on time to maximize the electrode reaction efficiency;
[0100] (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment with a power of 600 W for 10 min, washed with deionized water for 18 min, stirred and soaked in a 10 mol / L hydrochloric acid solution for acid washing for 3 h, solid-liquid separation, and solid drying to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film;
[0101] The silicon nanowires prepared in this embodiment were used as the silicon negative electrode material for lithium batteries to test their electrochemical properties. The testing method was carried out in accordance with the method in Appendix D of the national standard GB / T38823-2020. The first discharge specific capacity of the lithium battery silicon negative electrode was 713.22 mAh / g, and the first coulombic efficiency could reach 86.56%.
[0102] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A molten salt electrochemical method for preparing silicon nanowires from silicon waste using nickel in situ catalysis without a template, characterized in that: The specific steps are as follows: (1) dispersing a binder in deionized water, stirring at a temperature of 70 to 100° C. for 2 to 5 minutes to obtain a binder gel, grinding and mixing the binder gel with silicon waste to obtain a silicon waste-gel mixture, and sintering the silicon waste-gel mixture at a temperature of 100 to 200° C. for 5 to 20 minutes to obtain a bonding silicon material; (2) adding a nickel catalyst and a pore-forming agent to the bonding silicon material, grinding and mixing, and then pressing and molding to obtain an electrolytic precursor; (3) adding a peroxide additive to a molten salt electrolyte, uniformly heating the temperature to 500 to 900° C. in a vacuum or protective gas atmosphere and maintaining the temperature until the molten salt electrolyte is completely dissolved into a molten state, thereby obtaining a molten salt electrolyte; (4) using an electrolytic precursor as a reduction cathode and an inert electrode as an anode, using a porous solid oxide diaphragm to divide the molten salt electrolytic cell into an anode electrolytic cell and a cathode electrolytic cell, filling the anode electrolytic cell and the cathode electrolytic cell with molten salt electrolyte, inserting the reduction cathode into the molten salt electrolyte of the cathode electrolytic cell, and inserting the anode into the molten salt electrolyte of the anode electrolytic cell; (5) at a temperature of 700 to 900° C., electrolyzing the molten salt with a high-frequency pulse current and a low duty cycle for 5 to 25 minutes, then electrolyzing the molten salt with a medium-frequency pulse current and a medium duty cycle for 40 to 120 minutes, and then electrolyzing the molten salt with a low-frequency pulse current and a high duty cycle for 80 to 200 minutes; the frequency of the high-frequency pulse current is 1500 to 2000 Hz, and the low duty cycle is 10 to 16%; The frequency of the medium frequency pulse current is 1 / 5 to 2 / 5 of the high frequency pulse current, and the medium duty cycle is 1.6 to 2 times of the low duty cycle; the frequency of the low frequency pulse current is 1 / 30 to 1 / 8 of the medium frequency pulse current, and the high duty cycle is 2 to 2.5 times of the medium duty cycle; (6) After the electrolysis is completed, the cathode product is taken out, cooled to room temperature, and then subjected to ultrasonic treatment, water washing, soaking and acid washing, and drying in sequence to obtain silicon nanowires. The growth ends of the silicon nanowires are agglomerated and coated to form a nano-NiSi2 alloy film.
2. The molten salt electrochemical method for preparing silicon nanowires from silicon waste by in-situ catalysis of nickel without a template according to claim 1, characterized in that: The binder in step (1) is one or more of epoxy resin, polyurethane, acrylate, silicone glue, polyvinyl alcohol, water glass, aluminum phosphate, and polyamide, and the mass ratio of the binder to the silicon waste is (32-48):100; the silicon waste in step (1) is silicon ash in the production process of industrial silicon or silicon alloy, and the morphology is amorphous silicon dioxide microspheres with an average particle size of 0.1-50 μm.
3. The molten salt electrochemical method for preparing silicon nanowires from silicon waste by in-situ catalysis of nickel without a template according to claim 1, characterized in that: The nickel catalyst in step (2) is one or more of nickel (II) acetylacetone, nickel oxide, nickel chloride, nickel formate, and nickel dichloride (diphenylphosphinoethane); the pore-forming agent is one or more of urea, CaCl2, starch, polystyrene, (NH4)2SO4, and NH4HCO3.
4. The molten salt electrochemical method for preparing silicon nanowires from silicon waste by in-situ catalysis of nickel without a template according to claim 1 or 3, characterized in that: The mass ratio of the silicon waste in step (1) to the nickel catalyst and pore-forming agent in step (2) is 100:(2-8):(12-18).
5. The molten salt electrochemical method for preparing silicon nanowires from silicon waste by in-situ catalysis of nickel without a template according to claim 1, characterized in that: The peroxide additive in step (3) is one or more of sodium peroxide, potassium peroxide, magnesium peroxide, lithium peroxide, and strontium peroxide, and the amount of the peroxide additive added is 4 to 8 wt.% of the molten salt electrolyte.
6. The molten salt electrochemical method for preparing silicon nanowires from silicon waste by in-situ catalysis of nickel without a template according to claim 1 or 5, characterized in that: The molten salt electrolyte is one or more of chloride, fluoride, carbonate and nitrate.
7. The molten salt electrochemical method for preparing silicon nanowires from silicon waste by in-situ catalysis of nickel without a template according to claim 1, characterized in that: The protective gas in step (3) is helium, argon, nitrogen, neon or krypton.
8. The molten salt electrochemical method for preparing silicon nanowires from silicon waste by in-situ catalysis of nickel without a template according to claim 1, characterized in that: The material of the inert electrode in step (4) is one or more of platinum, graphite, glassy carbon, ruthenium oxide, and iridium oxide; the porous solid oxide diaphragm is yttrium-stabilized zirconium oxide, calcium-stabilized zirconium oxide, or lithium aluminum zircon phosphate, with a porosity of 32-40% and a pore size of 0.01-0.1 μm.
9. The molten salt electrochemical method for preparing silicon nanowires from silicon waste by in-situ catalysis of nickel without a template according to claim 1, characterized in that: In the step (4), the distance between the anode and the cathode is 15 to 45 mm.
10. The molten salt electrochemical method for preparing silicon nanowires from silicon waste by in-situ catalysis of nickel without a template according to claim 1, characterized in that: The ultrasonic power of step (6) is 500-1500w, and the time is 1-10min; the acid solution for pickling is one or more of HCl, H2SO4, HNO3, and HF, and the H + The concentration is 0.01~10mol / L, and the immersion pickling time is 0.5~4h.